Evaluación del Sistema de Riego Superficial practicado en la Comunidad la Portada, Cantón Mira Provincia del Carchi - Burbano Rosero, Luciano David (2019)
ABSTRAC The La Portada community located in the canton Mira of the province of Carchi, is inhabited by families of farmers who live thanks to their harvests of short cycle crops and fruit trees, due to their unfavorable climatic conditions for long dry periods, they saw the need to provide irrigation to their plots, for which 1996 they are organized forming an irrigation board called La Chimba ditch with the purpose of using the water resource of the creek of the same name. The board, complying with all the legal provisions, succeeded in allocating the use of water at a flow rate of 16.85 l/s for irrigation. With the sentence, the organization builds an open ditch from the bed of the creek to its premises without any catchment infrastructure. In 2011 the Provincial Government of Carchi, builds the catchment in concrete and a section of the pipeline with a diameter of 160 mm PVC in a length of 1300 m in diameter, from the take until the first delivery of the plots, the other driving is by open ditch in a length of 4000m. The board is constituted by 63 users, distributed the water with all the flow and with irrigation times of 3, 6, 9 and 12 hours, with a frequency of 15 days, the irrigation is applied in a general way in furrows. The evaluation showed that, due to the type of irrigation practiced, the efficiency of application is very low, due to the losses caused throughout the whole system, in addition the soil losses and the bad uniformity that causes diseases to their crops can be observed. Keywords: System, irrigation, water, crops, catchment, users.